Study of Heart Rate Variability in Bipolar Disorder: Linear and Non-Linear Parameters during Sleep - Migliorini, Matteo; Mendez, Martin O.; Bianchi, Anna M. (Frontiers in Neuroengineering, 2012)
In the present paper we propose a methodology for the assessment of the autonomic nervous system (ANS) in patients affected by bipolar disorder. ANS was explored by means heart rate variability (HRV) analysis carried out during night recordings through the evaluation of many different parameters in the time and in the frequency domain, linear and non-linear. The recording of the signals was performed by a wearable sensorized T-shirt. HRV with movement analysis allowed also sleep staging and the estimation of REM sleep percentage over the total sleep time. A group of 8 normal female constituted the control group, on which normality ranges were estimated. One pathologic subject was recorded during four different nights, at time intervals of at least one week, and during different phases of the disturbance. Some of the calculated parameters (MEANNN, SDNN, RMSSD) confirmed reduced HRV in depression and bipolar disorder. REM sleep percentage was found to be increased. LZC (Lempel Ziv complexity) and SampEn (Sample Entropy), on the other hand, seem to correlate with the depression level. Even if the number of examined subjects is small, and the results need further validation, the proposed methodology and the calculated parameters seem promising tools for the monitoring of mood changes in psychiatric disorders.